A Randomized Crossover Study on the Effects of Inhaled Rice Paddy Herb Oil (Limnophila aromatica (Lam.) Merr.) on Autonomic Nervous System and Reaction Time on Healthy Volunteers - Thanatuskitti, Pakamon; Siripornpanich, Vorasith; Sayorwan, Winai; Ruangrungsi, Nijsiri (Journal of The Royal Thai Army Nurses, 2020)
Rice paddy herb, a characteristic odor vegetable is commonly used in Thai dishes and Asian indigenous system of medicine. This study aimed to evaluate the effects of rice paddy herb aerial part essential oil inhalation on autonomic nervous system and reaction time tasks among healthy volunteers using a randomized crossover design. Twenty-four healthy participants aged between 18 and 25 years were received sweet almond oil and rice paddy herb oil (8% v/v in sweet almond oil) by inhalation. ANS activities were recorded using BIOM7000 Patient Monitor. The simple and choice reaction tasks were performed on computer screen by the Deary-Liewald reaction time program. Data were analyzed using paired t-test with a significance level of .05. Simple reaction times to responses as well as choice reaction correct items and times were recorded. The results showed that the rice paddy herb oil statistically significantly decreased the systolic blood pressure, diastolic blood pressure and heart rate. For reaction time tasks, the rice paddy herb oil statistically significantly decreased the responded times in simple reaction time test. In summary, the rice paddy herb oil affected systolic and diastolic blood pressure as well as heart rate and it showed potential on the reaction response improvement among healthy participants.